Comparative Analysis of User Satisfaction Levels of Threads and X Applications Using the PIECES Method - Nurul Rahmayani; Dolly Indra; Muhammad Arfah Asis (Jurnal Nasional Teknologi dan Sistem Informasi, 2024)
Technology and information systems are high-speed in their application in helping community activities in the digital era. People's desire to access the Internet has increased to provide opportunities for companies to provide technology services, namely the Internet. One of the latest platforms to gain popularity among young users is Threads, which Instagram launched. X is an online social networking and microblogging service that allows users to send and receive text-based messages or posts. To determine whether Threads and X can be used to the best of their ability to access information, an analysis of the performance of the applications was conducted. This study uses the PIECES method to determine user satisfaction with the Threads and X applications. This research uses the PIECES analysis method, which consists of several assessment indicators (Performance, Information and Data, Economics, Control, Security, Efficiency, and Service) by distributing questionnaires to active users of Threads and X from various regions to get 1002 respondents. The results of this study show that Threads receives an average score of 3.61, indicating that users are satisfied, while X gets an average score of 4.37, indicating that users are satisfied. So, the results of this study show that the average level of satisfaction of X users is more significant than Threads. This shows that X's average level of user satisfaction is superior to that of Threads.